Uruguay : Selected Issues. (IMF Staff Country Reports; Country Report, 2017)
This Selected Issues paper presents an overview of inter-sectoral exposures in Uruguay. The Uruguayan financial system has been characterized by solid balance sheets, a low level of credit, and continued high dollarization since the crisis in 2002. However, pockets of vulnerability remain, especially after the recent slowdown in economic growth. Nonfinancial public sector (NFPS) gross debt is fairly high at 48 percent of GDP. The NFPS as well as the public sector as a whole have a net open foreign currency position. The nonbank financial system also has a large exposure to government debt.